Manifestações neurológicas e psiquiátricas na cardiopatia reumática crônica - Luiz Paulo Bastos Vasconcelos (2020)
Background: Rheumatic heart disease (RHD) is the most serious manifestation of rheumatic fever resulting from an abnormal immune response to a streptococcal pharyngitis, which may also affect the brain. The present study assessed the prevalence of neurological and psychiatric disorders in RHD patients and clinical features associated with basal ganglia motor dysfunction. Methods: We conducted structured neurologic and psychiatric assessment in randomly selected patients with RHD among those routinely referred to a tertiary center for heart valve diseases. Validated questionnaires for the evaluation of cognition, depression, anxiety, and obsessive-compulsive symptoms were applied. Basal ganglia motor dysfunction (BGMD) was defined as the presence of clinically-determined involvement of motor frontostriatal circuits based on the detection of hyperkinetic movement disorders. Echocardiography was performed to assess the pattern of valvular involvement and RHD severity. Results: Fifty patients with age of 43.2 ± 10.8 years, 84% female, were included. The mitral valve was affected in 47 patients (94%), and 21 of them (42%) had also aortic valve involvement. Neurological and psychiatric disorders were frequent, including chorea (22%), chronic tics (18%), obsessive-compulsive symptoms (48%), major depression (34%) and generalized anxiety disorder (54%), cognitive complaints (66%), migraine (52%) and seizures (18%). The factors associated with clinical signs of BGMD were age (adjusted odds ratio [OR]: 0.916, 95% confidence interval [CI]: 0.853 - 0.985; p = 0.018), major depression (adjusted OR: 7.534, 95% CI: 1.528 - 37.148; p = 0.013), and Yale-Brown Obsessive Compulsive (Y-BOCS) score (adjusted OR: 1.101, 95% CI: 1.022 - 1.187; p = 0.011). The severity of heart disease was not associated with clinically-defined BGMD. Conclusions: Neurological and behavioral manifestations are frequent in RHD patients, which may persist up to 3 decades after acute rheumatic fever. Age, major depression and Y-BOCS score were independently associated with BGMD. These manifestations deserve a close attention of clinicians and researchers dealing with adults patients with RHD.